Krüppel-like factor-4 and Krüppel-like factor-2 are important regulators of joint tissue cells and protect against tissue destruction and inflammation in osteoarthritis. Issue 8 (9th May 2022) - Kawata, Manabu; Teramura, Takeshi; Ordoukhanian, Philip; Head, Steven R; Natarajan, Padmaja; Sundaresan, Aishwarya; Olmer, Merissa; Asahara, Hiroshi; Lotz, Martin K
Abstract : Objectives: Analysing expression patterns of Krüppel-like factor (KLF) transcription factors in normal and osteoarthritis (OA) human cartilage, and determining functions and mechanisms of KLF4 and KLF2 in joint homoeostasis and OA pathogenesis. Methods: Experimental approaches included human joint tissues cells, transgenic mice and mouse OA model with viral KLF4 gene delivery to demonstrate therapeutic benefit in structure and pain improvement. Mechanistic studies applied global gene expression analysis and chromatin immunoprecipitation sequencing (ChIP-seq). Results: Several KLF genes were significantly decreased in OA cartilage. Among them, KLF4 and KLF2 were strong inducers of cartilage collagen genes and Proteoglycan-4. Cartilage-specific deletion of Klf2 in mature mice aggravated severity of experimental OA. Transduction of human chondrocytes with Adenovirus (Ad) expressing KLF4 or KLF2 enhanced expression of major cartilage extracellular matrix (ECM) genes and SRY-box transcription factor-9, and suppressed mediators of inflammation and ECM-degrading enzymes. Ad-KLF4 and Ad-KLF2 enhanced similar protective functions in meniscus cells and synoviocytes, and promoted chondrocytic differentiation of human mesenchymal stem cells. Viral KLF4 delivery into mouse knees reduced severity of OA-associated changes in cartilage, meniscus and synovium, and improved pain behaviours. ChIP-seq analysis suggested that KLF4 directly bound cartilage signature genes. Ras-related protein-1 signalling was the most enriched pathway in KLF4-transduced cells, and its signalling axis was involved in upregulating cartilage ECM genes by KLF4 and KLF2. Conclusions: KLF4 and KLF2 may be central transcription factors that increase protective and regenerative functions in joint tissue cells, suggesting that KLF gene transfer or molecules upregulating KLFs are therapeutic candidates for OA.